1999
DOI: 10.1080/00016489950180685
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Human Uvula

Abstract: Eleven uvular biopsies were investigated for their morphology, the presence of mast cells and the distribution of hyaluronan and its major ligand CD44. Three microanatomical sites--surface epithelium, subepithelial area and area of glands--were examined. The oral side of the uvula was covered by a 15-20 cell thick layer of keratinized/parakeratinized surface epithelium, firmly anchored to the underlying connective tissue by connective tissue papillae. The width of the intercellular spaces in the epithelium inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Pendlebury et al 19 found that the mean apnea-hypopnea index increased from 22 to 33 events per hour over a mean period of 17 months. Neurogenic damage to upperairway muscles 20 and to the soft palatal mucosa, 21 and/or the formation of uvular edema, 22 possibly caused by the vibration and stretching of the tissues from snoring and apneas, may explain the progressive nature of the disease. The severity of the disease was unchanged in the present sample of patients during long-term treatment with mandibular advancement devices.…”
Section: Discussionmentioning
confidence: 99%
“…Pendlebury et al 19 found that the mean apnea-hypopnea index increased from 22 to 33 events per hour over a mean period of 17 months. Neurogenic damage to upperairway muscles 20 and to the soft palatal mucosa, 21 and/or the formation of uvular edema, 22 possibly caused by the vibration and stretching of the tissues from snoring and apneas, may explain the progressive nature of the disease. The severity of the disease was unchanged in the present sample of patients during long-term treatment with mandibular advancement devices.…”
Section: Discussionmentioning
confidence: 99%
“…Thickening of the tissue results. 29,30 Catalfumo and coworkers 31 performed endoscopy in 104 awake patients after unsuccessful UPPP in supine position and had the patients pant deeply. Twelve patients (11.5%) showed a dorsal displacement of the epiglottis of more than 45 degrees, obstructing the glottis completely.…”
Section: Discussionmentioning
confidence: 99%
“…Thickening of the tissue results. 29,30 Catalfumo and coworkers 31 performed endoscopy in 104 awake patients after unsuccessful UPPP in supine position and had the patients pant deeply. Twelve patients (11.5%) showed a dorsal displacement of the epiglottis of more than 45 degrees, obstructing the glottis completely.…”
Section: Discussionmentioning
confidence: 99%